Abidkulova K.T., Mukhitdinov N.M., Ametov A.A., Ivashchenko A.A., Ydyrys A., Tazhibaeva K. Seed production of rare, endemic plant Iris alberti under different ecological-coenotical conditions in trans – Ili Alatau mountains: Al-Farabi Kazakh National University, Almaty, Kazakhstan; 2 - Ile-Alatau State National Nature Park, Almaty, Kazakhstan (Eurasian Journal of Ecology, 2018)
In 2015, the authors investigated and found two populations and 4coenopopulations of Iris alberti in the Ile-Alatau State National NaturePark. In the article, the authors present the ecological-coenotical characteristics of plant communities with the participation of Iris alberti withinthe studied population and describe the characteristics of seed productionof this species. There were determined the number of generative shootsper 1 square meter, counted and measured fruit on them, the number ofseeds in them, and the size of the average weight of 1000 seeds. Analysisof the Iris alberti seed production in the investigated populations showedthat the percentage of flowering and fructification of this species under thein situ conditions were 48 – 62%, slightly higher than the ex situ conditions (33,3-39,1%). The average number of seeds, in a single generativeshoots were insignificant, only 45-91 pcs. According to conducted countsof fruit size, the number of seeds in them, the number of seeds on shootsand weight of 1000 seeds were higher in plants in the population 2, whichis probably due to the more favorable ecological and cenotical conditionsof this habitat.Key words: Iris alberti , seed production, population, cenopopulation